2023
DOI: 10.5267/j.uscm.2022.10.008
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cyber resilience and robustness on supply chain performance: Evidence from the UAE chemical industry

Abstract: This paper examines the impact of cyber resilience and supply chain (SC) robustness on supply chain performance in the UAE chemical industry. No prevailing empirical evidence makes this research unique and beneficial to the literature and future research related to cyber resilience in the chemical industry. Moreover, this research is a contemporary contribution to the research of the UAE chemical industry. The study applies a quantitative approach with causal, exploratory and analytical design. The magnitude o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 27 publications
0
45
0
Order By: Relevance
“…This style of leadership is committed to and empowers organizational learning, giving everything expected to confront the hindrances and troubles that may upset this learning (T M Ghazal et al, 2023b;Mat Som and Kassem, 2013;. This finding is additionally steady with Nafei et al ( 2012), who indicated that shared leaders help individuals to achieve the undertakings relegated to them, tune in to their requirements and wants, welcome and prize their new plans to unravel issues and try to create workers by using their forces to improve and create open doors for organizational learning (Muhammad Turki Alshurideh et al, 2023b). The current discoveries additionally uncovered that all the measurements that establish shared leadership apply a huge impact on organizational learning ability in banks (El .…”
Section: Relationship Between Shared Leadership and Organizational Le...mentioning
confidence: 81%
“…This style of leadership is committed to and empowers organizational learning, giving everything expected to confront the hindrances and troubles that may upset this learning (T M Ghazal et al, 2023b;Mat Som and Kassem, 2013;. This finding is additionally steady with Nafei et al ( 2012), who indicated that shared leaders help individuals to achieve the undertakings relegated to them, tune in to their requirements and wants, welcome and prize their new plans to unravel issues and try to create workers by using their forces to improve and create open doors for organizational learning (Muhammad Turki Alshurideh et al, 2023b). The current discoveries additionally uncovered that all the measurements that establish shared leadership apply a huge impact on organizational learning ability in banks (El .…”
Section: Relationship Between Shared Leadership and Organizational Le...mentioning
confidence: 81%
“…In Dubai, DEWA provides over 600,000 customers with electricity and over 500,000 customers with water (Al-Awamleh et al, 2022;Muhammad Alshurideh et al, 2023;. Looking and analyzing those numbers we can realize the need and the importance of collaborative system at DEWA and how it helps the company to manage its activities (Muhammad Turki Alshurideh et al, 2023b), various teams, and many projects effectively with minimal errors (Al- Al-Maroof et al, 2022b;Haitham M. Alzoubi et al, 2022f;.…”
Section: Dewa (Dubai Electricity and Water Authority) Company Profile...mentioning
confidence: 99%
“…Alshurideh et al [ 104 ] investigate supply chain (SC) robustness and cyber resilience effects on supply chain performance in the UAE chemical sector. Data is gathered from factories producing chemicals in Abu Dhabi, United Arab Emirates.…”
Section: Literature Reviewmentioning
confidence: 99%